Area Optimized FPGA-Based Implementation of The Sobel Compass Edge Detector. (7th March 2013) - Singh, Sanjay; Saini, Anil Kumar; Saini, Ravi; Mandal, A. S.; Shekhar, Chandra; Vohra, Anil
Abstract : This paper presents a new FPGA resource optimized hardware architecture for real-time edge detection using the Sobel compass operator. The architecture uses a single processing element to compute the gradient for all directions. This greatly economizes on the FPGA resources' usages (more than 40% reduction) while maintaining real-time video frame rates. The measured performance of the architecture is 50 fps for standard PAL size video and 200 fps for CIF size video. The use of pipelining further improved the performance (185 fps for PAL size video and 740 fps for CIF size video) without significant increase in FPGA resources.